A multimodal discourse analysis of the Moonlight movie poster - Fachri Rafi Rizqullah (Passage: Journal of English Language and Literature, 2024)
In the world of movie posters, it employs a fusion of visual design to carry out a special meaning. This study employs a descriptive qualitative method to conduct a detailed analysis of the multimodal discourse on the poster of Moonlight (2016). The analysis employed a Kress and Van Leeuwen’s (1996) framework of multimodal discourse analysis (MDA) namely representational meaning, interactional meaning and compositional meaning. The findings of the analysis on the movie poster of Moonlight (2016) show a rich and multi-layered representational meaning that softly depicts the protagonist’s journey of self-discovery and the challenges he faced in a culturally diverse and economically disadvantaged neighborhood. Interactional meaning is established through intentional visual choices, fostering intimacy.The compositional elements, including salience, information value, and framing techniques, contribute to the poster's visual appeal and thematic context. The poster serves as an intricate advertising piece, employing narrative and conceptual representations to depict the protagonist’s self-discovery journey within a socio-cultural context.